DETERMINATION OF COEFFICIENT OF CAPITALIZATION FROM STATISTICAL DATA - M. . Laskin; O. . Rusakov; O. . Dzhaksumbaeva (Статистика и экономика, 2016)
The article introduces a new stochastic model of the real estate market pricing, cost of rent, capitalization ratio appraisals based on a lognormal distribution. Statistical processing of Saint-Petersburg real estate market data results that the empirical distributions of the prices signicantly t to the two dimensional lognormal law of distribution. For establishing statistical hypotheses accordance we use Kolmogorov-Smirnov test of t. Basing on the Russian Federal standard FSO N2, we look to the market value as a numerical characteristic (mode) of a random value. We understand capitalization ratio as a random variable with the conditional lognormal distribution